(untitled) - McBee, Jim (San Francisco, 2004)
Advanced Coverage for Experienced Exchange Administrators Microsoft Exchange Server 2003 24seven doesn't try to take you back to square one. Instead, it builds on the knowledge you've already earned. Expert Jim McBee with assistance from Barry Gerber delivers targeted instruction and inside tips that will help you follow the best practices established by successful Exchange organizations across a wide range of industries. This is also a great way to make a smooth transition to the latest release of Exchange Server. Coverage includes: Getting your Exchange installation right the first time Managing interactions with Active Directory Understanding Exchange data storage Preventing and recovering from disasters Administering daily operations Customizing Exchange Optimizing performance Achieving higher availability Isolating and solving common Exchange problems Troubleshooting SMTP and DNS problems Improving security against viruses and worms Securing clients Deploying and customizing Outlook web access Supporting mobile clients.
Keywords: Client/server computing,Máy chủ/ máy khách,Microsoft Exchange server